Model Manajemen Krisis Public Relations (MPR) dalam Menghadapi Krisis di Era Pandemi Covid-19 - Rd. Nia Kania Kurniawati; Ail Muldi; Yoki Susanto; Neka Fitriyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
Public relations is a proactive management role that monitors trends, events, and concerns that may occur and detract from the company's critical relationships. When a crisis develops, the Public Relations' efforts to continuously monitor through informal relationships and others may be of great service to the organization. PR can therefore be considered a company's portrait. It is the organization's eyes, ears, and spokesperson at the same time. When an organization is in a state of instability, public relations takes the lead, when it is in a state of stability, it remains diligent in research and analysis, and when a firm advances, it stands behind and supports all of the organization's supporting activities and initiatives. In other words, Public Relations is an absolute necessity. PR serves as a facilitator and mediator between an organization and the public during a crisis. In my preamble, I underlined the importance of public relations in organizations, particularly in Indonesia, which, from my perspective, still gives PR meaning and places it in a significantly different position than it should.